Ewing sarcoma with initial presentation in mandible: A case report - Milanović Srđan; Milošević Nikola; Dožić Marko; Ristić Dušan; Stojković Goran; Miletić Nebojša (Serbian Medical Society - Dental Section, Belgrade, 2019)
Ewing sarcoma is a tumor that rarely occurs after the age of twenty. This tumor is even more rare in the region of head and neck, either as a primary site or a place of dissemination of the disease. Treatment is multidisciplinary and includes administration of chemotherapy, surgery and/or radiotherapy. This case report refers to the 29-year-old female patient who was referred to maxillofacial surgeon for tooth pain and swelling of the left side of mandible that was not solved after the antibiotic treatment. After a biopsy was performed, Ewing's sarcoma of the mandible was diagnosed, and primary localization in the pelvis was confirmed before starting the treatment. One year after chemotherapy and radiation treatment completion, there was no sign of disease. This case shows that all doctors specialized in oral and / or maxillofacial surgery, as well as medical doctors and dentists in primary health care, have important role in early diagnosis of these rare diseases, and thus contribute to better treatment outcomes, even in advanced cases.